Overview of the effect of rumen-protected limiting amino acids (methionine and lysine) and choline on the immunity, antioxidative, and inflammatory status of periparturient ruminants - Khan, Muhammad Zahoor; Liu, Shuai; Ma, Yulin; Ma, Mei; Ullah, Qudrat; Khan, Ibrar Muhammad; Wang, Jingjun; Xiao, Jianxin; Chen, Tianyu; Khan, Adnan; Cao, Zhijun (Frontiers in Immunology, 2023)
Overproduction of reactive oxygen species (ROS) is a well-known phenomenon experienced by ruminants especially during the transition from late gestation followed by successful lactation. This overproduction of ROS may leads to oxidative stress. The oxidative stress compromises the immunity and anti-inflammatory system of animals which predisposes them to health issues. Besides, during the periparturient period, metabolic stress is developed due to negative energy balance which is followed by excessive fat mobilization and poor production performance. Excessive lipolysis causes the immune-suppression, abnormal regulation and enhanced oxidative stress. Indeed, OS plays a key role in regulating various organs' metabolic activity and farm animal productivity. For example, rapid fetal growth and the production of large amounts of colostrum and milk, as well as an increase in both maternal and fetal metabolism, result in increased reactive oxygen species production and increased requirements for micronutrients, including antioxidants, during the last trimester of pregnancy and at the start of lactation. Oxidative stress is generally neutralized by the natural antioxidant system available in the body. However, in some special phases like the transition period, the animal’s natural antioxidant system is unable to cope with the situation. The effect of rumen-protected limiting amino acids and choline on regulation of immunity, anti-oxidative and anti-inflammatory status followed by better milk production performance has been widely studied in ruminants. Thus in the current review, we have discussed the research development on the positive effect of rumen-protected first limiting amino acids (Lysine and methionine) and choline on immunity, anti-oxidative and anti-inflammatory status followed by better production performance in ruminants especially during the perinatal and lactational stage.